DETERMINING THE INFLUENCING FACTORS OF THE INDONESIAN MARITIME SECURITY USING ANALYTICAL HIERARCHY PROCESS - Hozairi Hozairi; Buhari Buhari; Heru Lumaksono; Marcus Tukan (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2019)
Indonesia has several institutions to maintain maritime defense and security, but maritime security is not only determined by the number of authorized agencies but by many factors. This study aims to assess the factors and sub-factors that affect Indonesian maritime security. To achieve the research objectives, the method used is the Analytical Hierarchy Process (AHP) with six factors and twenty-nine sub-factors. The process of collecting data through questionnaires and interviews with several experts, the results of the questionnaire were taken with a Geometric Average, after which it was calculated according to the stages of the AHP method. The findings of this study produce priority factors that affect maritime security, first are defense and security factors (0.37), second is political and legal factors (0.24), third is economic factors (0.16), fourth are technological factors (0.11), fifth are social and cultural factors (0.07) and sixth are environmental factors (0.04). The contribution of this research is a consideration for the Government to determine policies towards improving maritime security in Indonesia.Keywords: Analytical Hierarchy Process, Determining, Maritime Security